Arsenic Contamination in Soil, Vegetable, Groundwater, and Riverine Fish Species in Joypurhat, Bangladesh - Md. Sakhawat Hossain; S. M. Abidur Rahman; Md. Mizanur Rahman; Md. Ali Muztaba; Uttam Ray (CV. Literasi Indonesia, 2022)
Arsenic contamination is one of the major concerns today in Bangladesh. Various potential and threatening health risks for humankind could be occurred due to the consumption of Arsenic which has mixed with the food chain like fish and vegetables. Therefore, in this study, we analyzed 100 samples of deep tube well water, sediment, soil, vegetable, and fish samples, collected from five different Upazila of Joypurhat district in Bangladesh. The farming process, unplanned groundwater consumption, etc. could be marked as the main culprit for arsenic contamination in a region. However, Arsenic concentrations were determined by atomic absorption spectroscopy followed by the wet digestion method. From this analysis, a shocking result has been found that almost every sample contains arsenic and its level crossed the permissible limit set by WHO guidelines for water and food samples (vegetable and rice) which is an alarming issue for southeast Asian countries.